2016
DOI: 10.1038/srep34043
|View full text |Cite
|
Sign up to set email alerts
|

Paraspeckles modulate the intranuclear distribution of paraspeckle-associated Ctn RNA

Abstract: Paraspeckles are sub-nuclear domains that are nucleated by long noncoding RNA Neat1. While interaction of protein components of paraspeckles and Neat1 is understood, there is limited information on the interaction of non-structural RNA components with paraspeckles. Here, by varying paraspeckle number and size, we investigate how paraspeckles influence the nuclear organization of their non-structural RNA component Ctn RNA. Our results show that Ctn RNA remains nuclear-retained in the absence of intact paraspeck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In some cases, the primary function may not be to regulate editing, but they nevertheless alter ADAR binding and editing. For example, BioID recovered many of the proteins found in paraspeckles, a complex ADAR1 had previously been found to be associated with (Anantharaman et al, 2016), highlighting the power of BioID to identify nearly all proteins found in a complex. We also found proteins that are ADAR interactors but not regulators of editing.…”
Section: Discussionmentioning
confidence: 92%
“…In some cases, the primary function may not be to regulate editing, but they nevertheless alter ADAR binding and editing. For example, BioID recovered many of the proteins found in paraspeckles, a complex ADAR1 had previously been found to be associated with (Anantharaman et al, 2016), highlighting the power of BioID to identify nearly all proteins found in a complex. We also found proteins that are ADAR interactors but not regulators of editing.…”
Section: Discussionmentioning
confidence: 92%
“…To evaluate whether the interaction between NONO and GSTP1 depends on paraspeckle formation, RNase digestion or si-NEAT1_2 transfection were used to destroy paraspeckle structure. 34 The results showed that destruction of paraspeckle structure suppressed GSTP1 binding to NONO or NEAT1_2 in IL-6-stimulated QGY-7703 cells ( Figure 7E, F). The data suggest that, besides trapping PRDX5 mRNA, IL-6-increased paraspeckle formation traps more GSTP1 proteins in the nucleus of HCC cells, leading to increased oxidative DNA damage.…”
Section: Prdx5 Interacts With Stat3 and Represses Stat3 Phosphorylatimentioning
confidence: 89%
“…S2B, C) to destroy the paraspeckle formation under IL-6 stimulation. 34 In Matrigel invasion assay, silencing of NEAT1_2 or NONO alone could not changed the migration of QGY-7703 and HepG2 cells, but significantly decreased IL-6-promoted migration of both cells ( Figure 3A). Furthermore, silencing of NEAT1_2 or NONO also suppressed IL-6-promoted cell cycle progression, with decreased S phase and increased G1 phase in NEAT1_2-or NONO-silenced QGY-7703 cells, and increased G1 phase and decreased G2/M phase in NEAT1_2-or NONO-silenced HepG2 cells, as compared with control cells after IL-6 stimulation ( Figure 3B).…”
Section: Paraspeckle Participates In Il-6-promoted Invasion and Survimentioning
confidence: 95%
“…NEAT1 is an essential component of nuclear paraspeckles [ 30 ], which contain ribonucleoprotein complexes formed around NEAT1 [ 9 ]. At present, NEAT1 is thought to be exclusive to the nucleus and mainly function as a transcriptional regulator.…”
Section: Discussionmentioning
confidence: 99%